Clonagem por estaquia de ramos de Dovyalis hebecarpa e Dovyalis hebecarpa X D. Abissinica - Alves, Ediane Conceição [UNESP] (2014)
Brazil is major producer of fruits and there is a niche market which is dominated by exotic fruit which has been widely accepted by consumers flavor aroma nutraceutical qualities as atractive. In this sense Dovyalis fits as a species with great potential to be among the exotic fruits sold in Brazil but larger studies concerning ways of obtaining seedlings are needed. Dovyalis (D. hebecarpa e Dovyalis hebecarpa x D. abissinica) belonging to the active ank of UNESP / FCAV / Jaboticabal - São Paulo were evaluated for the feasibility of cloning by cutting. +Herbaceous cuttings about 10 cm long with a pair of leaves at the apex had their bases immersed in alcoholic solution of butyric acid (IBA) at concentrations of 0; 1000; 3000 and 5000 mg L-1. Each experiment was replicated four times in distinct periods of the year: summer, autumn, winter and spring. The variables evaluated were: survival and rooting percentage besides average number and length of roots. The experimental design used was factorial randomized (DIC) in 2 x 4 x 4 (2 clones x 4 IBA concentrations x 4 seasons collect cuttings collection periods) with 4 replications and 10 cuttings per experimental parcel. No significant influence cuttings percentage reaching up to 100% in both clones. Regarding rooting, the collection periods during summer are the most suitable for the accomplishment of the cutting in both clones. For number and length of roots, no interaction was observed between all factors, only between clones and collection periods. Highest averages were reached in cuttings collected in autumn and winter for hybrid and for D. hebecarpa no statistical differences were observed between seasons. For the average root length both clones showed the best average with collection period during spring. We conclude that the propagation is possible for both clones and the summer season is most suitable for collecting material, without the ...